ETHOSOMES: A NOVEL APPROACH FOR THE DELIVERY OF DRUG - Muhammad Ahsan Waqar; Muhammad Zaman; Huma Hameed; Minahal Munir (International Journal of Pharmacy & Integrated Health Sciences)
Background: In the past m8any years, there have been many studies that are considering the nanoparticles as the carriers of the drugs for improving the patient compliance. One such approach of delivery of the drug is through the ethosomes. Objectives: This review aims to describe the vesicular approach of ethosomes that had been used to overcome the barrier for the transdermal delivery of drug and also describes brief composition, method of preparation, characterization tests, mechanism of penetration of ethosomes, as well as highlighted various studies of ethosomes in medicine. Methodology: Relevant data was searched using various databases like Google Scholar, PubMed, SpringerLink and Scopus. Results: Ethosomes are the vesicular shaped structures comprising majorly of phospholipids and ethanol. Due to their size in nanometers and presence of increased amount of the ethanol in its structure, it had shown very high permeation of the drug when given through the transdermal route or topically. There are basically two methods for the formulation of the ethosomes that includes the hot method and cold method. Furthermore, recently more two methods have also been developed for formulating ethosomes including classical mechanical dispersion method and transmembrane pH gradient method. After formulation of ethosomes, many characterization tests can be performed on ethosomes such as pH, particle size, zeta potential, in vitro permeation studies, microscopic evaluation and stability studies. Conclusion: Many more studies are needed to enhance these novel drug delivery systems and other vesicular systems such as transferosomes and invasomes for better therapeutic output and ultimately increasing the patient compliance.